Changes in Corneal Astigmatism after Closing Clear Corneal Incision by Simple Hydration Undergoing Phacoemulsification at the Department of Ophthalmology JPMC - Maria Kanwal, Muhammad Ali Tahir, Arif Rabani, Aziz Ur Rehman, Alyscia Cheema, Asim Ateeq, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: To determine the mean changes of corneal astigmatism after closing clear corneal incision by simple hydration undergoing phacoemulsification in the eye department of a tertiary care hospital. Methodology: This was a Quasi experimental study conducted at the department of Ophthalmology, Jinnah Postgraduate Medical Center, Karachi, from 30th October 2020 to 29th April 2021. Total 100 patients who underwent phacoemulsification surgery for cataract were included. Changes of astigmatism were measured with Auto-refractometer. Fundus examination was done using +90D lens with a slit lamp. Mean changes in corneal astigmatism were calculated. Pre and post operatively change in astigmatism was compared using paired t-test. Stratification was done. P value ≤0.05 was considered as statistically significant. Results: Mean age was 43.47±11.13 years. There were 54% male and 46% female patients. Mean change of corneal astigmatism was 0.23±0.44 diopter. Mean corneal astigmatism, preoperatively, after 1 week and after 1 month were 1.05±0.05 diopter, 0.69±0.34 diopter and 1.28±0.44 diopter respectively. Highly significant mean difference of corneal astigmatism was observed between preoperatively and after 1 week, preoperatively and after 1 month and also observed between 1 week and 1 month. Conclusion: Closing clear corneal incision by simple hydration undergoing phacoemulsification was found an effective technique for treatment of corneal astigmatism. Keywords: Mean Changes, Corneal Astigmatism, Closing Clear Corneal Incision, Simple Hydration, Phacoemulsification